Enhancing the academic success of competitive student athletes using a motivation treatment intervention (Attributional Retraining). (September 2016) - Parker, Patti C.; Perry, Raymond P.; Hamm, Jeremy M.; Chipperfield, Judith G.; Hladkyj, Steve
Abstract: Competitive student athletes who experience the typical challenges inherent in high school-to-university transitions must also overcome sport-related difficulties which can undermine their academic motivation and class attendance due to competitions, fatigue, injuries, identity issues, and novel training environments (MacNamara & Collins, 2010; Simons et al., 1999). In an eight-month quasi-experimental, randomized treatment field study, an attribution-based motivation treatment (Attributional Retraining: AR) was administered to student athletes ( n = 185) and non-athletes ( n = 281) who differed in perceived control beliefs (±1 SD) in a two-semester, online course. Simple slope regression analyses revealed the AR (vs. no-AR) treatment assisted competitive student athletes who had low control beliefs by increasing perceived success in the course ( b = 0.84, p = 0.038), post-treatment test performance ( b = 11.68, p = 0.001), year-end course grades ( b = 6.32, p = 0.017), and by reducing course withdrawals ( b = −1.00, p = 0.034, OR = 0.37). These results demonstrate the benefits of an attribution-based motivation treatment for vulnerable student-athletes in terms of perceived course success, performance, and persistence in making the transition from high school to college. Highlights: Athletes in college received a motivation treatment: Attributional Retraining (AR). AR facilitated academic performance for low perceived control student athletes. Low control athletes who received AR were 63% less likely to withdraw from a course. AR may be useful for athletic programs dealing with academic probation issues.